(untitled) (Research in Agriculture Livestock and Fisheries, 2017)
Among over 180 Aspergilli, Aspergillus fumigatus is the most common etiological agent causing invasive mold infection mostly in immunocompromised human and animal. Besides, the fungus is used for various useful purposes. However, for the utilization of A. fumigatus as a useful candidate, accurate identification is crucial. Here, the research work was aimed at identifying A. fumigatus from poultry feed samples using conventional and molecular techniques. Out of 23 feed samples, 2 (8.7%) were found to be positive for A. fumigatus. The internal transcribed spacer 1 (ITS 1) and ITS 2 regions and the 5.8S ribosomal DNA (rDNA) region of the fungus were amplified by polymerase chain reaction. The ITS regions are located between the 18S and 28S rRNA genes, and rRNA gene for 5.8S RNA separates these two ITS regions. The isolated gene has been sequenced and deposited in the GenBank (accession no. KC142152). The gene was 100% similar to other reference species of A. fumigatus, whereas in phylogenetic analysis, a clear distance was found in the cases of other Aspergilli. Based on the unique nature of the ITS1 and ITS2 regions and phylogenetic analysis of the genes, A. fumigatus was correctly identified. The isolated strain could be a good candidate for further studies especially for utilization in the field of biotechnology. Res. Agric. Livest. Fish.4(3): 165-171, December 2017